Analisis Miksonsepsi Siswa menggunakan Metode Four-Tier Diagnostic Test dengan Certainty of Response Index (CRI) pada Materi Suhu dan Kalor - Fakhruddin, Fakhruddin; Hauwali, Nikodemus Umbu Janga; Lantik, Vinsensius; Gelole, Maria Gelu (UNIVERSITAS INDRAPRASTA PGRI, 2024)
This research aimed to determine the misconceptions experienced by students of SMAN 1 Kupang City using the Four-tier Diagnostic Test method with the Certainty of Response Index. The approach used in this study is a quantitative approach with the type of research that is descriptive quantitative. In this research, the test was used to determine whether there were misconceptions and to know what extent the level of misconceptions experienced by students. The results showed that there were 35% of students who understood concepts in the medium category, as many as 23% of students did not understand concepts in the low category, 35% of students experienced misconceptions in the low category and 7% of errors in the low category. Based on data from research conducted at SMAN 1 Kupang City using the Four-tier Diagnostic Test method with CRI that has been carried out, it can be concluded that students of SMAN 1 Kupang City for the 2022/2023 school year experience misconceptions in temperature and heat material by 35% in the medium category